Characterization of New Wire Gauze High‐Capacity Structured Packing with Varied Inclination Angle. Issue 3 (9th February 2017) - Amini, Younes; Karimi-Sabet, Javad; Esfahany, Mohsen Nasr
Abstract: A new high‐capacity structured packing (PACK‐1300) was investigated for the separation of mixtures with low separation factor. The effect of the inclination angle was studied. In order to enhance the pressure drop and the separation efficiency of PACK‐1300, the surface area and porosity were increased. In addition, comprehensive parametric studies were performed to evaluate the dry/wet pressure drop and mass‐transfer efficiency under various operating conditions. Increasing the inclination angle enhances the capacity and decreases the efficiency of the packings. PACK‐1300W reduced the dry and wet pressure drop significantly more than PACK‐1300Z. Finally, the separation efficiency results show that the height equivalent to a theoretical plate decreased with decreasing inclination angle. Abstract : Distillation is an efficient and economic separation method with application in various industries. A new high‐capacity structured packing, PACK‐1300, with various inclination angles was investigated for the separation of mixtures with low separation factor. Parametric studies were performed to evaluate the dry/wet pressure drop and mass‐transfer efficiency under various operating conditions.